Pengembangan E-LKPD Eksperimen Berbasis Inkuiri Terbimbng Berbantuan Phyphox untuk Meningkatkan Pemahaman Konsep - Nora Nora; Lukman Hakim; Rita Sulistyowati (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2022)
This study is to describe the validity, practicality and effectiveness of the guided inquiry-based physics e-LKPD experimental guide on collision material assisted by the Phyphox application to improve students' conceptual understanding. This research is research and development, while the development model used is the ADDIE model. Methods of collecting research data with surveys, interviews and questionnaires. The results showed that the e-LKPD Physics experimental guide was generated as a whole from the assessment of several aspects of the three validators including the material aspect, an average value of 87% was obtained in the valid category, the language aspect obtained an average value of 87% in the valid category and the media aspect. obtained an average of 89% with a valid category. Then the value of the practicality of the product from the students obtained an average of 84.30% in the practical category. So that from distributing questionnaires about the product to validators and students, the product is declared suitable for use in a wider scope. While the effectiveness of students in using the product is obtained from the N-gain formula with an average value of 0.7 with a high category